2017
DOI: 10.1002/mnfr.201601046
|View full text |Cite
|
Sign up to set email alerts
|

Accurate assessment of alpha‐gal syndrome using cetuximab and bovine thyroglobulin‐specific IgE

Abstract: Differentiation of alpha-gal syndrome from patients with immediate allergy to meat consumption or asymptomatic sensitization requires quantification of cetuximab- or BTG-induced sIgE via detection of IgE for α-gal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…We also show that Tc-bovine antibodies have similar levels of α-gal compared with a human-derived IVIG. The α-gal causes a human-immunologic barrier to xenotransplantation or anaphylaxis/hypersensitivity reactions in some humans after equine antivenom or cetuximab administration or red meat consumption, and SAB-139 should not cause α-gal-related reactions [7,8,39]. Results from the recently completed phase I clinical trial in healthy adults for SAB-301 (anti-MERS CoV) [18] indicated that it was well tolerated, but further studies in humans to determine safety and/or immunogenicity will be needed for SAB-139 and other Tc-hIgG products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also show that Tc-bovine antibodies have similar levels of α-gal compared with a human-derived IVIG. The α-gal causes a human-immunologic barrier to xenotransplantation or anaphylaxis/hypersensitivity reactions in some humans after equine antivenom or cetuximab administration or red meat consumption, and SAB-139 should not cause α-gal-related reactions [7,8,39]. Results from the recently completed phase I clinical trial in healthy adults for SAB-301 (anti-MERS CoV) [18] indicated that it was well tolerated, but further studies in humans to determine safety and/or immunogenicity will be needed for SAB-139 and other Tc-hIgG products.…”
Section: Discussionmentioning
confidence: 99%
“…Several passive immunotherapeutics are under development to treat emerging infectious diseases and filoviruses [1][2][3][4][5][6]. However, traditional human-derived and heterologous animal-derived polyclonal immunoglobulins (Igs) and monoclonal antibodies can have lengthy development and/or clinical safety issues [1,7,8]. To address these shortcomings, genetically modified transchromosomic bovines (Tc-bovines) were developed that adaptively produce fully human polyclonal antibodies after exposure to environmental or vaccine antigens [9][10][11][12].…”
mentioning
confidence: 99%
“…* A definitive association between these tick species and AGS has not been experimentally proven in all these reports [see van Nunen (31)] .** The study by Sim et al (72) reported 11 cases of AGS, Lee et al (71) reported 1 case of AGS and van Nunen (44) reported that several more cases of this disease have occurred in Korea .…”
Section: Epidemiology Of Agsmentioning
confidence: 99%
“…SPT and sIgE for crude meat extracts such as beef, pork or lamb are known to be not valuable for the differential diagnosis of α-gal syndrome 27. Contrarily, sIgE for α-gal is known to have diagnostic value in α -gal syndrome 28. PROTIA™ Allergy-Q 64 Atopy ® detects IgE for α-gal using bovine thyroglobulin (bTG).…”
Section: Discussionmentioning
confidence: 99%